Mitigating Risks in Study Abroad with Grounded Theory Strategies : Mitigating Risks in Study Abroad (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
In a rapidly changing world, universities need to adapt to changes, be flexible, and assume that challenges and risks are part of education abroad. For this reason, working with a solid host partner with whom deep ties exist is fundamental for the success at mitigating risk in a post pandemic global context. Collaboration is clearly essential to support the faculty director’s roles and responsibilities.  Effective risk management is a key consideration for all nursing faculty directors to incorporate in a changed global healthcare environment and should be included from the onset in education abroad program development. One best practice is that U.S. higher education institutions and nursing departments collaborate with already known and trusted partners for nursing programs that include academic and service experiences for students.